Penciptaan Lagu Mars sebagai upaya memperkuat Nasionalisme terhadap Sekolah Indonesia Den Haag - Desti Yustianingsih; Fensy Sella; Henry Virgan; Gunar Gunadi (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Objective: This study aims to address the need of Sekolah Indonesia Den Haag (SIDH) for a school march song as a symbol of pride and an educational tool to instill national values within a multicultural environment. Method: The research employs a practice-led research (PLR) method with an artistic approach, involving a step-by-step creation process including lyric writing, idea and melody exploration, and musical composition. The process engages teachers, SIDH academic community members, and music experts, and includes documentation, discussions, and song trials with the school institution to ensure alignment with its values and needs. Results and Discussion: The main outcome of the research is the creation of an SIDH school march song that is easy to remember and carries a strong message of nationalism, fostering unity and a shared school identity. The documented creative process highlights collective involvement as a participatory approach in developing educational works. Conclusion: This study affirms the fundamental importance of a school march song in shaping identity, reinforcing national values, and nurturing nationalism in Indonesian educational environments abroad. Its novelty lies in meeting a real institutional need with a contextually relevant composition and providing a creative process model that may serve as a reference for other schools.